Theileria annulata infects B-cells in sheep, which display lower dissemination potential compared to T. lestoquardi-infected ovine B-cells - Shahin Tajeri; Perle Latré de Laté; Johanneke D. Hemmink; Christina Vrettou; Gordon Langsley; W. Ivan Morrison (Ticks and Tick-Borne Diseases)
Theileria annulata and Theileria lestoquardi are deadly tick-borne parasites of cattle and sheep, respectively. These parasites are transmitted by Hyalomma ticks, and their geographical distributions partially overlap, with T. annulata having a wider range. Theileria lestoquardi infection is highly pathogenic in its natural sheep and goat hosts while T. annulata infection usually causes a mild disease in these species. Interestingly, T. annulata does not produce merozoites/piroplasms in sheep and goats, therefore it is not tick-transmissible. The aim of the current study was to understand the basis of the attenuated pathogenicity of ovine infections by T. annulata. Theileria annulata and T. lestoquardi sporozoites were used to infect sheep and parasitized ovine leukocytes were isolated and phenotyped. This revealed that T. annulata sporozites target ovine B-cells, whereas T. lestoquardi sporozoite infection was not restricted to ovine B-cells. The ability of ovine B-cells infected with T. lestoquardi or T. annulata to traverse Matrigel in vitro was investigated, as a surrogate for their ability to disseminate in vivo and cause disease. The Matrigel traversal index of T. lestoquardi-transformed ovine B-cells was significantly higher than that of T. annulata-transformed ovine B-cells isolated from the same host, consistent with the reported diminished pathogenicity of T. annulata infections in sheep. Theileria lestoquardi-transformed ovine B-cells preferentially expressed matrix metalloproteinase 2 (mmp2), whereas T. annulata-infected ovine B-cells strongly expressed mmp9. Correspondingly, MMP9 protein levels and collagenase activity were higher in T. annulata-transformed ovine B-cells. However, T. annulata-transformed ovine B-cells expressed higher levels of transcripts for Tissue Inhibitor of Metallopeptidases 1 and 2 (TIMP1 and TIMP2). TIMPs are the natural endogenous inhibitors of MMPs. This argues that their heightened expression could underpin the significantly lower Matrigel traversal activity of T. annulata-infected compared to T. lestoquardi-infected ovine B-cells.